Anti-tumor activity and the mechanism of SIP-S: A sulfated polysaccharide with anti-metastatic effect. (20th September 2015) - Zong, Aizhen; Liu, Yuhong; Zhang, Yan; Song, Xinlei; Shi, Yikang; Cao, Hongzhi; Liu, Chunhui; Cheng, Yanna; Jiang, Wenjie; Du, Fangling; Wang, Fengshan
Highlights: SIP-S showed anti-tumor activity in vivo. SIP-S could improve the thymus and spleen indices of S180-bearing mice and the mice treated with cyclophosphamide. SIP-S could induced apoptosis in SKOV3 cells by regulating apoptotic protein expression in vitro . Abstract: Our previous studies demonstrated that SIP-S had anti-metastatic activity and inhibited the growth of metastatic foci. Here we report the anti-tumor and immunoregulatory potential of SIP-S. SIP-S could significantly inhibit tumor growth in S180-bearing mice, and the inhibition rates was 43.7% at 30 mg/kg d. Besides, SIP-S could improve the thymus and spleen indices of S180-bearing mice and the mice treated with CTX. The combination of SIP-S (15 mg/kg d) with CTX (12.5 mg/kg d) showed higher anti-tumor potency than CTX (25 mg/kg d) alone. These results indicated that SIP-S had immunoenhancing and anticancer activity, and the immunoenhancing activity might be one mechanism for its anti-tumor activity. Flow cytometry results showed that SIP-S could induce tumor cells apoptosis. Western blot analysis indicated that SIP-S could upregulate the expression of pro-apoptotic proteins, caspase-3, -8, -9 and Bax, and downregulate the expression of anti-apoptotic protein PARP-1 in tumor cells in a dose-dependent manner. In summary, SIP-S has anti-tumor activity, which may be associated with its immunostimulating and pro-apoptotic activity.